2004
DOI: 10.1111/j.1461-0248.2004.00614.x
|View full text |Cite
|
Sign up to set email alerts
|

Limited filling of the potential range in European tree species

Abstract: The relative roles of environment and history in controlling large-scale species distributions are important not only theoretically, but also for forecasting range responses to climatic change. Here, we use atlas data to examine the extent to which 55 tree species fill their climatically determined potential ranges in Europe. Quantifying range filling (R/P) as realized/potential range size ratios using bioclimatic envelope modelling we find mean R/P ¼ 38.3% (±30.3% SD). Many European tree species naturalize ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
733
5
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 637 publications
(783 citation statements)
references
References 35 publications
38
733
5
7
Order By: Relevance
“…One of the native species, P. aurea, is predicted to be suitable for all sites. These Wndings are consistent with other studies that have found that many, even well-dispersed plant species, such as north-temperate forest trees, do not occupy distributions that are fully in equilibrium with abiotic environmental conditions (Svenning and Skov 2004;Prince and Carter 1985). They also complement previous research showing that poorly dispersed CFR Proteaceae occupy less of their predicted potential ranges than well-dispersed species (Schurr et al 2007).…”
Section: Discussionsupporting
confidence: 81%
“…One of the native species, P. aurea, is predicted to be suitable for all sites. These Wndings are consistent with other studies that have found that many, even well-dispersed plant species, such as north-temperate forest trees, do not occupy distributions that are fully in equilibrium with abiotic environmental conditions (Svenning and Skov 2004;Prince and Carter 1985). They also complement previous research showing that poorly dispersed CFR Proteaceae occupy less of their predicted potential ranges than well-dispersed species (Schurr et al 2007).…”
Section: Discussionsupporting
confidence: 81%
“…Consequently, where woody species die over large areas of their latitudinal range, rapid replacement by more drought tolerant species is unlikely without human intervention owing to the dispersal lag of the incoming species [8,24,[80][81][82][83][84]. In such a scenario, recent studies demonstrate that, rather than observing ecotone shifts, ecotone expansions and rapid alterations to plant communities are likely to occur [4,5,8,41,46], including the formation of novel species assemblages driven by expansion of non-native species [8,85] or the absence of competitors [3].…”
Section: Genetic and Evolutionary Implicationsmentioning
confidence: 99%
“…Climate change may increase the extinction risk of already endangered species already threatened by small populations, low genetic diversity, habitat specialization or a limited geographic range (Moritz et al, 2008;Fordham et al, 2013). Most endangered species are specialists confined to restricted habitats, less physiologically tolerant to environmental change and less able to migrate/disperse to track climate change (Svenning and Skov, 2004;Maclean and Wilson, 2011). A major challenge in conservation planning for these species, in particular, is to incorporate climate change impacts into species conservation strategies (Araújo and Rahbek, 2006;Willis and Bhagwat, 2009;Strange et al, 2011).…”
Section: Introductionmentioning
confidence: 99%